Effect of tannin and amino acid supplementation on growth, digestibility, and blood parameters in heifer calves - LU'LU' NABILA SALSABILA; AINISSYA FITRI; FAJAR EDY MARETNO SITANGGANG; IDAT GALIH PERMANA; WARTIKA ROSA FARIDA; DWITAMI ANZHANY; RONI RIDWAN (Nusantara Bioscience, 2025)
Abstract. Salsabila LN, Fitri A, Sitanggang FEM, Permana IG, Farida WR, Anzhany D, Ridwan R. 2025. Effect of tannin and amino acid supplementation on growth, digestibility, and blood parameters in heifer calves. Nusantara Bioscience 17: 194-201. Nutritional management during the growth phase of heifer calves is crucial for optimal performance and health. Tannins and amino acids have shown potential benefits in ruminant nutrition through improved protein utilization and antimicrobial properties. This study aimed to evaluate the effect of tannins (1% DM), amino acids (0.3% DL-methionine + 0.7% L-lysine), and their mixture on heifer calves' performance and metabolic indicators. To achieve the objective, a 4 × 4 Latin square design was used with 4 calves (109.00 ± 18.17 kg of body weight), each receiving 4 treatments in 4 periods. The treatment period lasted 14 days, including 10 days for diet adaptation and 4 days for sample collection. The basal diet was a Total Mixed Ration (TMR) consisting of 20 kg/d of forage and 2 kg/d of concentrate. Treatments included: P1 (control, TMR only), P2 (TMR + 1% dry matter intake (DMI) tannin), P3 (TMR + 1% DMI amino acids), and P4 (TMR + 1% DMI tannin and 1% DMI amino acids). The results showed that individual supplementation in P2 (0.66 kg/h/d) and P3 (0.73 kg/h/d) had higher Average Daily Gain (ADG) compared to P1 (0.54 kg/h/d) and P4 (0.41 kg/h/d) (p < 0.05). Feed efficiency in P2 (2.65%) and P3 (3.02%) is higher than in P1 (2.49%) and P4 (1.74%) (p < 0.05). Although nutrient intake did not differ, Crude Protein (CP) intake in the P1 (0.32 kg/day) was lower than in the P2 (0.44 kg/day), P3 (0.39 kg/day), and P4 (0.40 kg/day) (p < 0.05). Plasma protein and cholesterol levels were lower in the P1 (7.07 g/dL; 94.14 mg/dL) than those (7.46-7.62 g/dL; 125.98-149.85 mg/dL, respectively) (p < 0.05). Overall, supplementation of 1% DMI tannin or amino acids alone improved the performance without compromising hematological profiles and blood metabolites.